Auracyanin A from the thermophilic green gliding photosynthetic bacterium Chloroflexus aurantiacus represents an unusual class of small blue copper proteins. - Van Driessche, G. (Cold Spring Harbor Laboratory Press, 1999)
The amino acid sequence of the small copper protein auracyanin A isolated from the thermophilic photosynthetic green bacterium Chloroflexus aurantiacus has been determined to be a polypeptide of 139 residues. His58, Cys123, His128, and Met132 are spaced in a way to be expected if they are the evolutionary conserved metal ligands as in the known small copper proteins plastocyanin and azurin. Secondary structure prediction also indicates that auracyanin has a general beta-barrel structure similar to that of azurin from Pseudomonas aeruginosa and plastocyanin from poplar leaves. However, auracyanin appears to have sequence characteristics of both small copper protein sequence classes. The overall similarity with a consensus sequence of azurin is roughly the same as that with a consensus sequence of plastocyanin, namely 30.5%. We suggest that auracyanin A, together with the B forms, is the first example of a new class of small copper proteins that may be descendants of an ancestral sequence to both the azurin proteins occurring in prokaryotic nonphotosynthetic bacteria and the plastocyanin proteins occurring in both prokaryotic cyanobacteria and eukaryotic algae and plants. The N-terminal sequence region 1-18 of auracyanin is remarkably rich in glycine and hydroxy amino acids, and required mass spectrometric analysis to be determined. The nature of the blocking group X is not yet known, although its mass has been determined to be 220 Da. The auracyanins are the first small blue copper proteins found and studied in anoxygenic photosynthetic bacteria and are likely to mediate electron transfer between the cytochrome bc1 complex and the photosynthetic reaction center.